Multiple Treatments of Pediatric Constraint-Induced Movement Therapy (pCIMT): A Clinical Cohort Study - DeLuca, Stephanie C. (Am J Occup Ther, 2015)
Pediatric constraint-induced movement therapy (pCIMT) is one of the most efficacious treatments for children with cerebral palsy (CP). Distinctive components of pCIMT include constraint of the less impaired upper extremity (UE), high-intensity therapy for the more impaired UE (≥3 hr/day, many days per week, for multiple weeks), use of shaping techniques combined with repetitive task practice, and bimanual transfer. A critical issue is whether multiple treatments of pCIMT produce additional benefit. In a clinical cohort (mean age = 31 mo) of 28 children with asymmetrical CP whose parents sought multiple pCIMT treatments, the children gained a mean of 13.2 (standard deviation [SD] = 4.2) new functional skills after Treatment 1; Treatment 2 produced a mean of 7.3 (SD = 4.7) new skills; and Treatment 3, 6.5 (SD = 4.2). These findings support the conclusion that multiple pCIMT treatments can produce clinically important functional gains for children with hemiparetic CP.